Respiratory Failure and Hypercoagulable State in Creutzfeldt-Jakob Disease: A Rare Case Report - Kurniawan, Celine; Manggala, Sidharta Kusuma (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2025)
Background:Creutzfeldt-Jakob Disease (CJD) is a rare, rapidly progressive neurodegenerative disorder caused by prion proteins. It is characterized by a variety of neurological symptoms that lead to severe cognitive decline and death. The uniqueness of this case lies in the severe complications of respiratory failure and a hypercoagulable state, which are not commonly highlighted in the literature. Reporting this case underscores the critical need for awareness and management strategies for such complications in CJD patients, which can significantly impact their clinical outcomes and quality of life.Case Illustration:A 69-year-old female presented with progressively worsening neurological symptoms over a short period. Initially, she experienced visual disturbances and hallucinations, followed by a rapid decline in consciousness, the onset of seizures, and myoclonus. Diagnostic investigations, including an electroencephalogram (EEG) and Magnetic Resonance Imaging (MRI), confirmed the diagnosis of Creutzfeldt-Jakob Disease (CJD).As her condition deteriorated, the patient developed pneumonia and septic shock. Excessive salivary secretion, a symptom often overlooked in CJD, led to significant respiratory compromise and failure. She was admitted to the intensive care unit (ICU) and required mechanical ventilation. Due to the prolonged need for ventilation and to manage airway secretions better, a tracheostomy was performed.Management of her respiratory failure involved meticulous care to reduce hypersalivation and prevent micro-aspiration. Regular suctioning of secretions was crucial. Additionally, given her immobility and increased risk of thromboembolism, she received prophylactic heparin to prevent venous thromboembolism. Physiotherapy was initiated to maintain limb mobility, and elastic stockings were used to reduce the risk of deep vein thrombosis.Conclusion:This case report highlights the complex clinical challenges in managing a patient with CJD, particularly the severe respiratory and thromboembolic complications. The comprehensive approach to managing respiratory failure through tracheostomy and proactive measures to prevent thromboembolism was essential in stabilizing the patient. However, the incurable nature of CJD meant that the focus ultimately shifted to palliative care. This case underscores the importance of recognizing and managing secondary complications in CJD to improve patient outcomes and the need for ongoing research into effective treatments for this devastating disease.